2016
DOI: 10.1063/1.4973429
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged silicon carbide integrated circuit operation in Venus surface atmospheric conditions

Abstract: The prolonged operation of semiconductor integrated circuits (ICs) needed for long-duration exploration of the surface of Venus has proven insurmountably challenging to date due to the ∼ 460 °C, ∼ 9.4 MPa caustic environment. Past and planned Venus landers have been limited to a few hours of surface operation, even when IC electronics needed for basic lander operation are protected with heavily cumbersome pressure vessels and cooling measures. Here we demonstrate vastly longer (weeks) electrical operation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 21 publications
1
34
0
1
Order By: Relevance
“…Out of possible electronics technologies identified for enabling improvements to Venus surface missions (Kolawa et al, ), only one technology has thus far experimentally demonstrated the ability to electrically function for prolonged duration in Venus surface atmospheric conditions. Recently, Neudeck et al () demonstrated operation of two silicon carbide (SiC) junction field effect transistor based ring oscillator integrated circuits (ICs) in a 21‐day test inside the Glenn Extreme Environments Rig (GEER) which is capable of simulating the high‐temperature and pressure extremes of Venus as well as reproduce conditions of the gas mixture expected at the Venus surface. Neudeck et al () describe multiple aspects of that testing relevant to the components' electrical durability; this paper addresses elements of material analysis not addressed in that paper such as the substantial chemical changes that occurred on some electrical connectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of possible electronics technologies identified for enabling improvements to Venus surface missions (Kolawa et al, ), only one technology has thus far experimentally demonstrated the ability to electrically function for prolonged duration in Venus surface atmospheric conditions. Recently, Neudeck et al () demonstrated operation of two silicon carbide (SiC) junction field effect transistor based ring oscillator integrated circuits (ICs) in a 21‐day test inside the Glenn Extreme Environments Rig (GEER) which is capable of simulating the high‐temperature and pressure extremes of Venus as well as reproduce conditions of the gas mixture expected at the Venus surface. Neudeck et al () describe multiple aspects of that testing relevant to the components' electrical durability; this paper addresses elements of material analysis not addressed in that paper such as the substantial chemical changes that occurred on some electrical connectors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Neudeck et al () demonstrated operation of two silicon carbide (SiC) junction field effect transistor based ring oscillator integrated circuits (ICs) in a 21‐day test inside the Glenn Extreme Environments Rig (GEER) which is capable of simulating the high‐temperature and pressure extremes of Venus as well as reproduce conditions of the gas mixture expected at the Venus surface. Neudeck et al () describe multiple aspects of that testing relevant to the components' electrical durability; this paper addresses elements of material analysis not addressed in that paper such as the substantial chemical changes that occurred on some electrical connectors. It is important to understand the degradation occurring on these connectors and associated materials so they can be redesigned in some way to assure survivability to meet the mission requirements.…”
Section: Introductionmentioning
confidence: 99%
“…2) resistor's V S = 0 V and V S = -25 V measured I-V's at 27 °C and 500 °C. The SPICE NMOS modeled I-Vs (dashed green) provide far better match to measured (dashed light blue) compared to the linear SPICE R model (solid blue), especially for V S ≈ -25 V substrate bias conditions employed in 1000+ hour 500 °C integrated circuit demonstrations to date [1][2][3][4].…”
Section: Methodsmentioning
confidence: 99%
“…1(a)]. The choice of these materials was motivated by three points: (i) experimental data is available for the temperature dependence of the gap [19,20] and band edges [17], (ii) SiC based semiconductor devices have been successfully tested at high temperatures (around 800 K) for Venus mission [21], where deep insight into the electron-phonon interaction of electronic bands has an uttermost importance, and (iii) SiC is a semiconductor platform for hosting hybrid opto-electro-mechanical defect quantum bits [22][23][24][25][26][27][28][29][30][31][32]. These defect quantum bits require very accurate electrical and optical control which depends on the ionization thresholds, i.e., the position of band edges at the operation temperature [33][34][35].In this Letter, we apply density functional theory (DFT) on the electronic structure and phonons in 4H and 6H SiC, and determine the electron-phonon coupling within Heine-Allen-Cardona (HAC) approach.…”
mentioning
confidence: 99%
“…39) because of a larger number of typical nitrogen donors ionization at k and h sites at 120 and 60 meV [49], respectively, with increasing temperatures. This paves the way for space agencies to employ 4H SiC based integrated circuits to probe the surface of Venus, where the temperature is ≈730 K [21].…”
mentioning
confidence: 99%